COMPARISON BETWEEN OF THE “BUMI MANUSIA” NOVEL BY PRAMOEDYA ANANTA TOER AND “BUMI MANUSIA” FILM BY HANUNG BRAMANTYO - Novia Nur Afsani; Sumaiyah Menjamin; Herman J. Waluyo; Budhi Setiawan (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
Popular novels always attract the attention of producers to make them into films with or without changes. The purpose of this research is to describe (1) comparison between the novel Bumi Manusia by Pramoedya Ananta Toer and Hanung Bramantyo's Bumi Manusia film from the ecranisation process (shrinking, adding, and change of variation) to the plot, setting, and character and (2) relevance of comparison results between novel and film Bumi Manusia as learning material at senior high school (SHS) or vocational high school (VHS). This research includes qualitative research with main data source is the novel and film Bumi Manusia. The sampling technique for this research uses purposive sampling. The data analysis technique used is interactive analysis. The results of the study can be described as follows: (1)The ecranisation of the novel to the film Bumi Manusia consists of 45 shrinks, 28 additions, and 35 changes in variations. In the plot ecranisation consists 33 shrinks, 18 additions, and 21 changes to variations. In setting ecranisation, consists 6 shrinks, 2 additions, and 8 changes in variation. In character ecranisation there are 6 shrinks, 8 additions, and 10 changes in variation. (2)Bumi Manusia novel can be an alternative to literary learning, especially novels in SHS or VHS because it has relevance to learning of the basic competency 3.9 dan 4.9 in class XII 2013 curriculum.